The type III secretion system and its role in the multicellular behaviour of Yersinia species - Barratt, Natalie Alice (2018)
Pathogenic Yersinia translocate Yersinia outer protein (YOP) effectors directly into eukaryotic cells via a virulence plasmid (pYV/pCD1)-encoded type III secretion system (T3SS) injectisome, where they interfere with host signalling pathways and inhibit inflammatory responses. A temperature of 37°C is required for injectisome assembly and YOP export is triggered by host cell contact or chelation of calcium ions. Yersinia pseudotuberculosis and Yersinia pestis both utilise N-acylhomoserine lactone (AHL) -dependent quorum sensing (QS), a process of signal molecule mediated cell-to-cell communication for coordinating gene expression within a bacterial population. In Y. pseudotuberculosis, T3S, motility, auto-aggregation (AAg) and biofilm formation on Caenorhabditis elegans are all under QS control.